MYTHSAND FACTS ABOUTTHEINTELLIGENCE ANDTALENT - De Zubiría Samper, Julián (2014)
These lines summarize the main findings on intelligence and talent that gets the author after following for nearly two decades to more than a thousand children of very superior intellectual abilities. The findings show that many myths persist about the concepts of intelligence and talent that should unveil today. Before them, the Colombian educator underpin the need to recognize different intelligences; modifiability of each, the lack of reliable evaluation for psychometric tests, the need to understand the talent of a composite manner, and the central role of environment and mediators in the development of both the intelligence and the talent.